2017
DOI: 10.2519/jospt.2017.7380
|View full text |Cite
|
Sign up to set email alerts
|

Hip Abductor Muscle Volume and Strength Differences Between Women With Chronic Hip Joint Pain and Asymptomatic Controls

Abstract: Study Design Secondary analysis, cross-sectional study Background Chronic hip joint pain (CHJP) can lead to limitations in activity participation, but the musculoskeletal factors associated with the condition are relatively unknown. Understanding the factors associated with CHJP may help develop rehabilitation strategies to improve quality of life of individuals with long-term hip pain. Objectives To compare measures of hip abductor muscle volume and hip abductor muscle strength between women with CHJP and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 37 publications
(54 reference statements)
0
39
0
Order By: Relevance
“…While previous studies have found evidence of gluteus medius muscle atrophy in association with severe hip osteoarthritis (Grimaldi et al, ; Zacharias et al, ), this is the first study to find evidence of specific hip abductor muscle atrophy in the presence of intra‐articular hip joint pathology in a younger, active population. In contrast, previous research found hip abductor muscle volume to be larger in young active patients with chronic hip joint pain compared with asymptomatic controls (Mastenbrook et al, ). However, it is important to note that this previous study did not measure size of the individual hip abductor muscles, but measured a region of interest that incorporated the gluteal group including the gluteus minimus, gluteus medius, and a small portion of the gluteus maximus muscles (Mastenbrook et al, ).…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…While previous studies have found evidence of gluteus medius muscle atrophy in association with severe hip osteoarthritis (Grimaldi et al, ; Zacharias et al, ), this is the first study to find evidence of specific hip abductor muscle atrophy in the presence of intra‐articular hip joint pathology in a younger, active population. In contrast, previous research found hip abductor muscle volume to be larger in young active patients with chronic hip joint pain compared with asymptomatic controls (Mastenbrook et al, ). However, it is important to note that this previous study did not measure size of the individual hip abductor muscles, but measured a region of interest that incorporated the gluteal group including the gluteus minimus, gluteus medius, and a small portion of the gluteus maximus muscles (Mastenbrook et al, ).…”
Section: Discussionmentioning
confidence: 70%
“…In contrast, previous research found hip abductor muscle volume to be larger in young active patients with chronic hip joint pain compared with asymptomatic controls (Mastenbrook et al, ). However, it is important to note that this previous study did not measure size of the individual hip abductor muscles, but measured a region of interest that incorporated the gluteal group including the gluteus minimus, gluteus medius, and a small portion of the gluteus maximus muscles (Mastenbrook et al, ).…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…3,5,46,116 These clinical signs are thought to be impacted by alterations in muscle size, quality and activity in hip-related pain. [117][118][119] Identifying whether differences in muscle activity and morphology exist between people with hip-related pain and those without, is a key consideration in the development of future exercise based interventions. Deficits in strength in hip-related pain have been associated with greater symptoms in people scheduled for hip arthroscopy.…”
Section: Management Of Hip-related Painmentioning
confidence: 99%